Alban and St Albans
1 online resource
Keywords: This is a collection of eighteen papers presented at a conference that was held at the Hatfield Campus of the University of Hertfordshire with 122 members and guests from the United Kingdom, the United States of America, Germany and Norway were present. The papers are on the research on various aspects of the art and architecture of the abbey, at St Albans and provides an ideal forum for bringing together many aspects of the abbey's history.